The Influence of Career Adaptability and Work Motivation on Employee Performance Mediated by Work Engagement - Dwi Nur Fitriani; Lie Liana (LP2M IAIN Palopo, 2026)
This study aims to analyze the influence of career adaptability and work motivation on employee performance mediated by work engagement. This study uses a quantitative approach with a population of 97 State Civil Apparatus (ASN) at OPD Kecamatan Ngaliyan, Semarang City. Data were processed using SPSS software version 29. Data analysis techniques include respondent descriptions, variable descriptions, validity tests, reliability tests, F tests, R² tests, t tests, and Sobel Tests. The results of the study state that career adaptability has a positive effect on work engagement, work motivation has a positive effect on work engagement, career adaptability has a positive effect on employee performance, work motivation has a positive effect on employee performance, work engagement has a positive effect on employee performance, work engagement mediates the effect of career adaptability on employee performance, and work engagement mediates the effect of work motivation on employee performance.